Malignant tissues produce divergent antibody glycosylation of relevance for cancer gene therapy effectiveness - Dominik Brücher; Vojtech Franc; Sheena N. Smith; Albert J. R. Heck; Andreas Plückthun (Taylor & Francis Group, 2020)
Gene therapy approaches now allow for the production of therapeutic antibodies by healthy or cancerous human tissues directly in vivo, and, with an increasing number of gene delivery methods available, the cell type for expression can be chosen. Yet, little is known about the biophysical changes introduced by expressing antibodies from producer cells or tissues targeted by gene therapy approaches, nor about the consequences for the type of glycosylation. The effects of different glycosylation on therapeutic antibodies have been well studied by controlling their glycan compositions in non-human mammalian production cells, i.e., Chinese hamster ovary cells. Therefore, we investigated the glycosylation state of clinically approved antibodies secreted from cancer tissues frequently targeted by in vivo gene therapy, using native mass spectrometry and glycoproteomics. We found that antibody sialylation and fucosylation depended on the producer tissue and the antibody isotype, allowing us to identify optimal producer cell types according to the desired mode of action of the antibody. Furthermore, we discovered that high amounts (>20%) of non-glycosylated antibodies were produced in cells sensitive to the action of the produced antibodies. Different glycosylation in different producer cells can translate into an altered potency of in-vivo produced antibodies, depending on the desired mode of action, and can affect their serum half-lives. These results increase our knowledge about antibodies produced from cells targeted by gene therapy, enabling development of improved cancer gene therapy vectors that can include in vivo glycoengineering of expressed antibodies to optimize their efficacies, depending on the desired mode of action.